Integration of computer technology in teacher education at Pakistan public sector university - Sadruddin Bahadur Qutoshi; Tajuddin Ddin Sharar; Sabit Rahim; Lourdes Bárbara Alpizar Caballero (Revista Cubana de Medicina Militar)
Introduction: Qualitative case study aims to explore the perceived practices of teacher educators about technology integration in their pedagogical engagement in B. Ed (Hons), elementary program offered by a public sector mountainous university in Pakistan. Objective: To explore the practices perceived by university teachers on the Integration of Computer Technology in Teacher Education to achieve the learning outcomes of the new four-year model B. Ed, to enable educators to improve their academic competence, and related professional competence, in the current, ongoing climate of educational reform. Methods: Qualitative case study research, theoretical and empirical methods were used; semi-structured and open Skype interviews were applied, based on an intentional sample of two teachers. Results: the teachers integrated computer technology in their teaching but the nature of integration was superficial. Conclusions: The new four-year model B. Ed used, was based in teacher-centered instead of learner-centered, the level of integration was symbolic. The institutional conditions in terms of resources, proficient level of knowledge and skills presented weaknesses, and improper organizational arrangements for technology integration in teaching. Authors recommended developing teachers' knowledge and pedagogical content knowledge of computer technology to improve 'essential conditions' required for successful integration of technology in teaching.